Rethinking specificity in defeasible reasoning and its effect in argument reinstatement - Bodanza, Gustavo Adrian (2017)
The principle of reinstatement governing most argument systems states that an argument is reinstated when all its defeaters are in turn ultimately defeated. Nevertheless, some criticisms to this principle have been offered in the literature. We found that problems arise when arguments in a chain of attacks are related by specificity: when non-maximally specific arguments are reinstated, fallacious justifications are originated. Particularly, we show how the problem affects DeLP, a system that combines a specificity-based defeat criterion with a reinstatement-based warrant process. Following old intuitions by philosopher Carl Hempel we rethink the concept's role within defeasible argumentation. Two kinds of specificity defeaters are identified: proper defeaters and cautious defeaters. While proper defeaters are well-known, cautious defeaters are formally introduced here. A system combining cautious and proper defeaters is defined as an extension of DeLP, and dialectic warrant games are proposed for filtering out non-maximally specific arguments.